ChemInform Abstract: Divergent Reactivity of Rhodium(I) Carbenes Derived from Indole Annulations. Issue 13 (March 2016) - Li, Xiaoxun; Li, Hui; Song, Wangze; Tseng, Po‐Sen; Liu, Lingyan; Guzei, Ilia A.; Tang, Weiping
Abstract: Propargylic alcohol substrates bearing an aryl ring with ortho N‐SO2 ‐aryl groups are treated with 2 equiv.